Respuesta :
Answer:
[tex]a+b+c=9+8+6=23[/tex]
Step-by-step explanation:
Let’s first simplify our expression. We have:
[tex]\displaystyle {\sqrt2+\frac{1}{\sqrt2}+\sqrt3+\frac{1}{\sqrt{3}}[/tex]
For the second term, multiply both the numerator and denominator by √2. This yields:
[tex]\displaystyle \frac{1}{\sqrt{2}}\cdot\frac{\sqrt{2}}{\sqrt{2}}=\frac{\sqrt{2}}{2}[/tex]
Similarly, for the fourth term, multiply both the numerator and denominator by √3. This yields:
[tex]\displaystyle\frac{1}{\sqrt{3}}\cdot\frac{\sqrt{3}}{\sqrt{3}}=\frac{\sqrt{3}}{3}[/tex]
Hence, our expression is now:
[tex]\displaystyle =\sqrt{2}+\frac{\sqrt{2}}{2}+\sqrt{3}+\frac{\sqrt{3}}{3}[/tex]
Let’s combine them. First, we will need common denominators.
Our denominators are 2 and 3. So, our common denominator will be its LCM.
The LCM of 2 and 3 is 6.
Hence, let’s make each term’s denominator 6.
For the first term, we can multiply both layers by 6. Hence:
[tex]\displaystyle \sqrt{2}=\frac{6\sqrt{2}}{6}[/tex]
For the second term, we can multiply both layers by 3. Hence:
[tex]\displaystyle \frac{\sqrt{2}}{2}=\frac{3\sqrt{2}}{6}[/tex]
For the third term, we can multiply both layers by 6. Hence:
[tex]\displaystyle \sqrt{3}=\frac{6\sqrt{3}}{6}[/tex]
And for the last term, we can multiply both layers by 2. Hence:
[tex]\displaystyle \frac{\sqrt{3}}{3}=\frac{2\sqrt{3}}{6}[/tex]
So, our expression is:
[tex]\displaystyle =\frac{6\sqrt{2}}{6}+\frac{3\sqrt{2}}{6}+\frac{6\sqrt{3}}{6}+\frac{2\sqrt{3}}{6}[/tex]
Add:
[tex]\displaystyle =\frac{6\sqrt{2}+3\sqrt{2}+6\sqrt{3}+2\sqrt{3}}{6}[/tex]
Combine like terms:
[tex]\displaystyle=\frac{9\sqrt{2}+8\sqrt{3}}{6}[/tex]
This cannot be simplified. So, c is as small as possible.
Hence: a=9, b=8, and c=6.
Therefore:
[tex]a+b+c=9+8+6=23[/tex]